Advances in pediatric cardiac MRI. Issue 5 (October 2016) - Banka, Puja; Geva, Tal
Abstract : Purpose of review: Spurred by numerous recent technological advances, cardiac MRI (CMR) is now the gold standard for anatomic evaluation, quantitative assessment of chamber size and function, flow quantification, and tissue characterization. This review focuses on recent advances in pediatric and congenital CMR, highlighting recent safety data, and discussing future directions. Recent findings: CMR has become an important component of risk stratification and procedural planning in numerous congenital and pediatric heart diseases. Innovative approaches to image acquisition and reconstruction are leading the way toward fast, high-resolution, three- and four-dimensional datasets for delineation of cardiac anatomy, function, and flow. In addition, techniques for assessing the composition of the myocardium may help elucidate the pathophysiology of late complications, identify patients at risk for heart failure, and assist in the evaluation of therapeutic strategies. Summary: CMR provides invaluable morphologic, hemodynamic, and functional data that help guide diagnosis, assessment, and management of pediatric and adult congenital heart disease. As imaging techniques advance and data accumulate on the relative and additive value of CMR in patient care, its role in a multimodality approach to the care of this population of patients is becoming clear and is likely to continue to evolve.